Carrier sense aware multipath geographic routing protocol. Issue 9 (30th April 2015) - Bennis, Ismail; Fouchal, Hacene; Zytoune, Ouadoudi; Aboutajdine, Driss
Abstract: Over the last few years, wireless sensor networks have become a great field of interest for the scientific community. This novel kind of network provides an array of applications for different aspects of human life. To give a satisfying performance to the final user, the wireless sensor networks must ensure the quality of service. The use of multipath technique was widely applied in the literature. Nevertheless, there might be a problem if the interference issues are not taken into account by the multipath routing design. In this paper, we propose a novel multipath routing protocol called Carrier Sense Aware Multipath Geographic Routing protocol (CSA‐MGR). This protocol creates multiple paths while avoiding any shared carrier sense range by using a distributed and dynamic process. In addition, the CSA‐MGR employs a new metrics named the Number of Common Neighbors to guarantee a faster and an efficient path construction. Simulations conducted over the NS‐2 simulator show promising results in terms of delay, Packet Delivery Ratio and routing overhead. The performance gain of CSA‐MGR in terms of delay is up to 275% compared with the Two‐Phase geographical Greedy Forwarding and up to 565% compared with the ad hoc on‐demand multipath distance vector. For the Packet Delivery Ratio, the performance gain of CSA‐MGR is up to 16% compared with the Two‐Phase geographic Greedy Forwarding and up to 28% compared with the ad hoc on‐demand multipath distance vector. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We propose a new routing protocol called Carrier Sense Aware Multipath Geographic Routing. Our protocol can find multipath while avoiding the carrier sense range effect. The simulation results show great performance against ad hoc on‐demand multipath distance vector and two‐phase geographical greedy forwarding.